Coercive, normative and Mimetic pressures as drivers of environmental management accounting adoption - Latif, Badar; Mahmood, Zeeshan; Ong, Tze San; Mohd Said, Ridzwana; Bakhsh, Allah (Multidisciplinary Digital Publishing Institute, 2020)
This paper explores the impact of institutional pressures on the adoption of environmental management accounting (EMA). EMA has been recognized as a valuable mechanism to deal with environmental issues. This paper uses institutional theory to explain the drivers of EMA adoption in Pakistan. Data were collected from the manufacturing sector in Pakistan through a questionnaire-based survey. The study concludes that coercive, normative and mimetic pressures have a significant and positive impact on the adoption of EMA.